Plausible Drying and Wetting Scenarios for Summer in Southeastern South America - Mindlin, Julia (2023)
Summer rainfall trends in southeastern South America (SE-SA) have received attention in recent decades because of their importance for climate impacts. More than one driving mechanism has been identified for the trends, some of which have opposing effects. It is still not clear how much each mechanism has contributed to the observed trends or how their combined influence will affect future changes. Here, we address the second question and study how the CMIP6 summer SE-SA rainfall response to greenhouse warming can be explained by mechanisms related to large-scale extratropical circulation responses in the Southern Hemisphere to remote drivers (RDs) of regional climate change. We find that the regional uncertainty is well represented by combining the influence of four RDs: tropical upper-tropospheric amplification of surface warming, the delay in the stratospheric polar vortex breakdown date, and two RDs characterizing recognized tropical Pacific SST warming patterns. Applying a storyline framework, we identify the combination of RD responses that lead to the most extreme drying and wetting scenarios. Although most scenarios involve wetting, SE-SA drying can result if high upper-tropospheric tropical warming and early stratospheric polar vortex breakdown conditions are combined with low central and eastern Pacific warming. We also show how the definition of the SE-SA regional box can impact the results since the spatial patterns characterizing the dynamical influences are complex and the rainfall changes can be averaged out if these are not considered when aggregating. This article’s perspective and the associated methodology are applicable to other regions of the globe.